Effect of age, cerebral infarcts, vasculopathy and haemoglobin on cognitive function, in Tanzanian children with sickle cell anaemia. (March 2022) - Jacob, Mboka; Stotesbury, Hanne; Kija, Edward; Saunders, Dawn; Mtei, Rachel J.; Tutuba, Hilda; Masanu, Upendo; Kilonzo, Mrema; Kazema, Ramadhan; Hood, Anna M.; Kirkham, Fenella; Dimitriou, Dagmara; et al.
Abstract: Background: Developmental difficulties in many cognitive domains are common in children with sickle cell anaemia (SCA). Children with stroke are most affected but delayed or atypical cognitive function has been reported in children with SCA and silent infarcts (SCI), vasculopathy, and normal brain MRI. However, very few studies of cognition have been conducted in Africa, a continent with 75% of the SCA burden. We therefore investigated cognitive profiles in Tanzanian children with SCA and examined the impact of age, SCI, vasculopathy, and haemoglobin concentration (Hb). Methods: Children aged 6–16 years with and without SCA were eligible for this cross-sectional study. Cognitive assessment was performed using Raven's Matrices, assessing fluid, non-verbal intelligence and subtests from the Wechsler Intelligence Scales for Children (WISC-IV), assessing processing speed (PS), perceptual reasoning (PR), and working memory (WM) as these tests are less culture-bound. Magnetic resonance imaging (MRI) and angiography (MRA) were also completed to assess the presence of SCI and vasculopathy. Hb was collected in both SCA children and their non-SCA siblings. Results: Seventy-three children with SCA and 71 healthy siblings (Meanages 11.9, SD = 2.8 and 11.1, SD = 2.9 years respectively) were recruited. Compared with healthy siblings, children with SCA had lower PS (Meandiff 7.35 points; p  = .002). Older children had higher performance scores on all tests in relation to their ages. Lowest cognitive scores were observed on the PS subtest, where patients with SCI (SCI+) had lowest mean values as compared to children with no SCI (SCI-) and healthy siblings (i.e., SCI+ < SCI- < healthy siblings, p = .028). On post-hoc analysis the difference was between SCI+ and healthy siblings SCI+ < non-SCA siblings (p = .015); there was no difference between SCI+ and SCI- patient groups. PS was significantly lower in SCA patients with no vasculopathy as compared to healthy siblings. The mean difference from healthy siblings was -8.352 and -0.752 points for VASC- and VASC + respectively ( p  = .004). There was a significant positive effect of Hb on PSI (p = .001) in both patients and controls and a trend level significant positive effect of Hb on PR ( p  = .050) and WM (p = .051). Conclusion: In this Tanzanian study, cognitive performance was reduced in children with SCA with or without SCI on MRI or vasculopathy. Cognitive performance improved with increasing age. Lower Hb was associated with lower cognitive performance in both patients with SCA and their non-SCA siblings. SCI and vasculopathy do not appear to have an impact on cognitive function.